1996
DOI: 10.1097/00000542-199611000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Omission of Nitrous Oxide during Anesthesia Reduces the Incidence of Postoperative Nausea and Vomiting

Abstract: Omission of nitrous oxide reduced the odds of postoperative nausea and vomiting by 37%, a reduction in risk of 28%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(64 citation statements)
references
References 58 publications
1
54
0
9
Order By: Relevance
“…In addition to studies showing that N 2 O increases postoperative nausea and vomiting [26][27][28], there are also studies showing that it has no effect [17,29,30].The effective prophylaxis and treatment would be diminish the risk of PONV [31]. Furthermore another meta-analysis show that the influence of N 2 O on PONV, with its relative risk approximately 1.4, is relatively low [32]. Also, Apfel et al [33], pointed out the main cause of early (0-2 h) PONV is the use of volatile anesthetics rather than N 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to studies showing that N 2 O increases postoperative nausea and vomiting [26][27][28], there are also studies showing that it has no effect [17,29,30].The effective prophylaxis and treatment would be diminish the risk of PONV [31]. Furthermore another meta-analysis show that the influence of N 2 O on PONV, with its relative risk approximately 1.4, is relatively low [32]. Also, Apfel et al [33], pointed out the main cause of early (0-2 h) PONV is the use of volatile anesthetics rather than N 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no signifi cant difference between the groups with and without N 2 O in the prevalence of nausea and vomiting at the postoperative 0-2 hours, there was a signifi cant difference in the nausea at the postoperative 2-24 hours and the frequency of antiemetic use (20,(23)(24)(25)(26). The mechanism of nausea and vomiting due to N 2 O establishes via intraabdominal distension, besides via stimulation of CTZ or nausea center in medullae (3). Despite the fact that the mean IAP was 7.6 cm-H 2 O in the group in which N 2 O had been administered, and 5.36 cmH 2 O in the group in which N 2 O had not been administered in our study, the incidence of nausea and vomiting was found to be 5 % in both groups.…”
Section: Tab 3 the Mean Arterial Pressure Values Of The Groups (Meamentioning
confidence: 93%
“…Although the rate of moderate-severe intestinal distention was 23 % in the fi rst and 9 % in the second group, the incidence of postoperative nausea and vomiting was similar (20). Although there was no signifi cant difference between the groups with and without N 2 O in the prevalence of nausea and vomiting at the postoperative 0-2 hours, there was a signifi cant difference in the nausea at the postoperative 2-24 hours and the frequency of antiemetic use (20,(23)(24)(25)(26). The mechanism of nausea and vomiting due to N 2 O establishes via intraabdominal distension, besides via stimulation of CTZ or nausea center in medullae (3).…”
Section: Tab 3 the Mean Arterial Pressure Values Of The Groups (Meamentioning
confidence: 96%
See 1 more Smart Citation
“…Omission of N 2 O significantly reduced PONV in several meta-analyses, [10][11][12][13] but the risk of intraoperative awareness was also increased. 12 In most meta-analyses, propofol was associated with a lower frequency of PONV when used for total iv anesthesia in the absence of N 2 O.…”
Section: Résultats : Aucune Différence Intergroupe N'a éTé Enregistrémentioning
confidence: 95%